Pengaruh Waktu Tunggu Antrian terhadap Kepuasan dan Niat Berkunjung Kembali di Kopi Klotok - Hendrajaya, Agnestasya Monica Putri; Pratika, Diah Agih; Veronica, Audiea; Afif, Fuadi; Hermawan, Hary; Ghani, Yosef Abdul (Jurnal Kajian Pariwisata, 2025)
This study aims to analyze the effect of waiting time duration on tourists' intention to revisit, with a particular emphasis on the mediating role of tourist satisfaction. Data were collected through a survey of tourists and analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The results show that waiting time duration has a significant effect on tourist satisfaction, which subsequently influences their intention to return (path coefficient = 0.451, p = 0.000). These findings confirm that tourist satisfaction acts as an important mediator in the relationship between waiting time and revisit intention. Therefore, effective waiting time management not only enhances satisfaction but also contributes to the development of tourist loyalty toward the destination. Optimizing waiting time becomes a key strategy in creating positive and sustainable tourism experiences.